A new species of Dinothenarus (Coleoptera: Staphylinidae) from Mexico - Santiago-Jiménez, Quiyari J. (Zootaxa, 2008)
Dinothenarus (s. str.) amisadaiae Santiago-Jiménez, sp. n. is described based on specimens from Cofre de Perote Volcano, Veracruz. The habitus and aedeagus are illustrated and distributional and biological data provided. A key to species of Dinothenarus (s. str.) of America is also provided. The discovery of this species in the high mountains of central Mexico represents a significant range extension for the genus Dinothenarus, previously known in Mexico only from Baja California, and especially for the subgenus Dinothenarus (s. str.), previously known only from northern North America and Eurasia.